Hemocyte-pericardial cell interaction during the growth of the dorsal vessel - Cevik, Duygu (My University, 2016)
Drosophila melanogaster has a tubular heart called the dorsal vessel, which is composed of contractile cardiomyocytes and hemolymph filtering pericardial cells. During larval development the dorsal vessel (heart) grows in size, and the luminal space inside the heart expands, however it has not been clear which cells are responsible for laying the extracellular matrix (ECM) during this expansion. Hemocytes (white blood cells), pericardial cells and cells of the fat body are candidate cell types that may secrete ECM for assembly during the growth of the heart lumen. With gene knock-down techniques we are exploring whether hemocytes participate in assembly of the heart ECM at this location. Additionally, studies of fluorescently tagged hemocytes in intact larvae reveal that hemocytes aggregate around pericardial cells of the dorsal vessel in 3rd instars. Confocal studies of dissected larval hearts indicate that hemocytes aggregate within infoldings of basement membrane associated with pericardial cells. Hemocyte-pericardial cell association could indicate that hemocytes take up proteins that are produced by pericardial cells and deliver them to other locations or that there might be a previously unidentified hematopoietic site at the Drosophila larval heart.
Keywords: Drosophila melanogaster; Hemocyte; Pericardial cell; Dorsal vessel; Extracellular matrix